A novel smart coating with ammonia-induced switchable superwettability for oily wastewater treatment. Issue 5 (October 2020) - Liu, Weiyi; He, Yingge; Zhang, Yanzong; Liu, Yan; Long, Lulu; Shen, Fei; Yang, Gang; Zhang, Xiaohong; Zhang, Shirong; Deng, Shihuai
Graphical abstract: Highlights: A smart PFDTMS/UA@TiOx coating with switchable wettability was fabricated. Superhydrophilicity-in air superoleophobicity was switched upon ammonia vapor. Used in oily wastewater treatment with high efficiency and good reusability. Superamphiphobicity can be recovered as before by heating. Synthetic mechanism of PFDTMS/UA@TiOx coating was explained. Abstract: Controllable superwettability has aroused increasing attention in the field of oily wastewater treatment, but its controllable preparation is still challenging. Herein, a smart superamphiphobic coating is reported, which become superhydrophilic and superoleophobic when it is induced by ammonia. This superamphiphobic coating is prepared by immersing into the fluorosilane-modified titanium carboxylate hybrid gel and the carnauba wax solution. Its superamphiphobicity is restored by heating to 65℃ for 15 min or by exposure to sunshine for 30 min. The as-prepared coating with switchable superwettability displayed outstanding oil-water selective separation performance, along with excellent durability. Its separation efficiency was always maintained at over 96.6 %, even after repeated use for 20 times. Collectively, this novel coating can be used for controllable oil and water separation, oil collection and water removal from oil, which stands for a developed treatment for oily wastewater.